Competition law in emerging economies : the Jamaican experience - Malahoo, Marlene P. (Centre of European Law LondonGB, 2000)
Provides an insight into the Jamaican experience. Considers the importance of competition policy and law. Looks at the background against which the Fair Competition Act was passed and focuses on the Fair Trading Commission. Analyzes the main competition law provisions. Emphasizes the importance of economics in every competition law analysis given that competition policy is essentially about economic behaviour. Seeks to provide some guidance in the approach to be taken by those involved in the application of the law. Reviews actions under the Act.